The Normalized Difference Vegetation Index and Angular Variation of Surface Spectral Polarized Reflectance Relationships: Improvements on Aerosol Remote Sensing Over Land - Han Wang (American Geophysical Union (AGU), 2019)
Abstract Surface polarized reflectance is related to its optical properties and observation geometry. It disturbs remote sensing of aerosol. In this study, we differentiated the polarized reflectance of a natural surface based on the normalized difference vegetation index and scattering angle, and the interband correlation coefficients were generally higher than that without differentiation. The spectral relationship was determined based on normalized difference vegetation index and scattering angle and then employed for aerosol retrieval from polarization and anisotropy of reflectances for atmospheric sciences coupled with observations from a lidar measurements. The retrieved aerosol optical depths (AODs) were contrasted with Aerosol Robotic Network results. The correlation coefficient between the retrieved and Aerosol Robotic Network AODs increased from 0.723 to 0.836, and the root‐mean‐square error reduced from 0.348 to 0.245 after considering the differentiated relationship. Thus, the accuracy of the retrieved AOD values was improved.